2019
DOI: 10.1167/19.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Gap effect and express saccades generation in amblyopia

Abstract: We did not observe any significant difference in terms of express saccades production between the control and amblyopic subjects. Our findings may suggest that amblyopia does not alter physiological mechanisms related to the efficiency of visual attention/fixation disengagement as supported by the observation that the gap effect and express saccades production was comparable between the normal and amblyopic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that the reduced saccade latency in gap trials is due to the reduced activity of fixation neurons in the superior colliculus [91]. Two recent studies examined the gap effect in adults with amblyopia [92, 93]. Results showed faster saccade latency for gap trials across all viewing conditions suggesting that disengagement of visual attention is not affected by amblyopia.…”
Section: Effects Of Amblyopia On the Oculomotor Systemmentioning
confidence: 99%
“…It has been suggested that the reduced saccade latency in gap trials is due to the reduced activity of fixation neurons in the superior colliculus [91]. Two recent studies examined the gap effect in adults with amblyopia [92, 93]. Results showed faster saccade latency for gap trials across all viewing conditions suggesting that disengagement of visual attention is not affected by amblyopia.…”
Section: Effects Of Amblyopia On the Oculomotor Systemmentioning
confidence: 99%
“…More generally, amblyopia affects a broad range of sensory functions in both the amblyopic ( Asper, Crewther, & Crewther, 2000a ; Asper, Crewther, & Crewther, 2000b ; Baker, Meese, & Hess, 2008 ; Hess, Thompson, & Baker, 2014 ; Hess & Howell, 1977 ; Levi, 2020 ; Levi & Harwerth, 1977 ; Mullen, Sankeralli, & Hess, 1996 ; Pardhan & Gilchrist, 1992 ) and non-amblyopic fellow eye ( Birch, Jost, Wang, Kelly, & Giaschi, 2019 ; Meier & Giaschi, 2017 ). These sensory deficits impact visuomotor behaviors such as saccadic eye movements ( Ciuffreda, Kenyon, & Stark, 1978a ; Ciuffreda, Kenyon, & Stark, 1978b ; Gambacorta, Ding, McKee, & Levi, 2018 ; Mackensen, 1958 ; Niechwiej-Szwedo, Goltz, Chandrakumar, Hirji, & Wong, 2010 ; Niechwiej-Szwedo, Chandrakumar, Goltz, & Wong, 2012 ; Perdziak, Witkowska, Gryncewicz, Przekoracka-Krawczyk, & Ober, 2014 ; Perdziak, Witkowska, Gryncewicz, & Ober, 2016 ; Perdziak, Gryncewicz, Witkowska, Sawosz, & Ober, 2019 ; von Noorden, 1961 ) and hand-eye coordination ( Grant, Melmoth, Morgan, & Finlay, 2007 ; Grant & Conway, 2015 ; Grant & Moseley, 2011 ; Melmoth, Finlay, Morgan, & Grant, 2009 ; Niechwiej-Szwedo, Goltz, Colpa, Chandrakumar, & Wong, 2017 ; Niechwiej-Szwedo, Colpa, & Wong, 2019 ). In particular, saccadic and manual response times are significantly delayed for stimuli viewed through the amblyopic eye ( Gambacorta et al, 2018 ; Hamasaki & Flynn, 1981 ; Levi, Harwerth, & Manny, 1979 ).…”
Section: Introductionmentioning
confidence: 99%